2020
DOI: 10.1007/s00438-020-01674-w
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of carotene biosynthesis leads to abnormal plastids and variegated leaves in Brassica napus

Abstract: Leaf color is an important characteristic of normal chloroplast development. Variegated plants have green-and white-sectored leaves, which can be used to identify important pathways and molecular mechanisms of chloroplast development. We studied two Brassica napus variegation mutants from same one variegated ancestor, designated ZY-4 and ZY-8, which have different degrees of variegation. When grown in identical conditions, the ratio of white sectors in ZY-4 leaves is higher than in ZY-8. In both mutants, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
(84 reference statements)
2
6
0
Order By: Relevance
“…By contrast, the reduced NtLCYB expression caused leaf variegation in the RNAi lines, as reported for other mutants in Arabidopsis, Brassica napus, and rice, with defects in carotenoid biosynthesis (Aluru et al, 2001;Aluru et al, 2009;Fang et al, 2008;Zhao et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…By contrast, the reduced NtLCYB expression caused leaf variegation in the RNAi lines, as reported for other mutants in Arabidopsis, Brassica napus, and rice, with defects in carotenoid biosynthesis (Aluru et al, 2001;Aluru et al, 2009;Fang et al, 2008;Zhao et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…S4B-D), points towards pigment, photosynthesis, and chloroplast biogenesis defects in these lines. Moreover, other carotenoid-defective mutants, and specially pds3 mutants, showed impaired chloroplast differentiation, development, and reduced chloroplast number (Aluru et al, 2001;Qin et al, 2007;Zhao et al, 2020). Carotenoids are located in the photosynthetic membrane in the form of chlorophyll-carotenoid-protein complexes and some carotenogenic enzymes are membraneassociated (Cunningham and Gantt, 1998;Green and Durnford, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cymbidium sinense , the ethylene response factors (ERFs) gene CsERF2 played crucial roles in leaf variegation [ 13 ]. Moreover, data showed that disruption of carotene biosynthesis in Brassica napus also led to abnormal plastids and variegated leaves [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analyzed species had higher Chla contents than any other photosynthetic pigment (Figure 2). This fact is widely discussed in several studies [5,[17][18][19][20][21] since Chla operates as the central molecule responsible for capturing light energy. This way, it can boost the electron transport reactions in the first stage of photosynthesis [19].…”
Section: Discussionmentioning
confidence: 96%